Relationship between Females’ Demographic Data and Pap Smear Test at Basrah City - Mansoor, Elaf Zuhair; Lamis Aziz Hameed; Hayat Yahya Shubbar (Indonesian Journal on Health Science and Medicine, 2025)
Abstract. The most popular and economical screening technique for identifying cervical cancer is the Pap test, which has also proved successful in lowering the incidence and related death rates in women. Aims this research to identify the Relationship between Females’ Demographic Data and Pap Smear Test at Basrah City. A cross-sectional research design. The study population consisted of all women who visited the screening center between January 1, 2013, and December 31, 2015. During this time, 677 women had pap smears and cytological examinations; of these, approximately 60.7% had normal results, 18.8% had LSIL, 4.3% had HSIL, 1% had SCC and adenocarcinoma, 1.2% had ASC-US and AGS-US, and 14% had inflammation. The prevalence of abnormal Pap smear increases with an increase in age, about 27.6% of LSIL and HSIL at age 40 and older. A significant relationship between Pap smear results of women who attended the cervical cancer screening center in Basrah and the following factors: passive smoking, duration of marriage, and parity. No significant relationship was found between Pap smear results and the following factors: age at first marriage and first pregnancy, number of husbands’ wives, socioeconomic status, and education level. Highlights: Abnormal Pap smear results were detected in 39.3% of women, with the prevalence increasing significantly after age 40. Significant associations were found between Pap smear outcomes and parity, duration of marriage, and passive smoking. No significant relationship was observed with age at first marriage, first pregnancy, socioeconomic status, or education level.